2012
DOI: 10.5301/ijao.5000066
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Hemodynamic Evaluation of Ventricular Suction Conditions of the EVAHEART Ventricular Assist Pump

Abstract: Purpose: Mismatches between pump output and venous return in a continuous-flow ventricular assist device may elicit episodes of ventricular suction. This research describes a series of in vitro experiments to characterize the operating conditions under which the EVAHEART centrifugal blood pump (Sun Medical Technology Research Corp., Nagano, Japan) can be operated with minimal concern regarding left ventricular (LV) suction. Methods: The pump was interposed into a pneumatically driven pulsatile mock circulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…11,25,36,38,45,54,63,64,[67][68][69][70]73 In these cases, ventricular blood flow was simulated either as a generic sinusoidal waveform or using pulsatile pumps that could change the stroke volume, heart rate and systolediastole ratio. More sophisticated MCLs considered either part 12,[16][17][18][19]22,23,[30][31][32][33][34][35]46,48,52,60,61,65,66,74 or all the cardiovascular system 13,14,29,39,40,49,50,53,75 by including compliance chambers and variable resistances or, in few cases, by simulating it computationally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,25,36,38,45,54,63,64,[67][68][69][70]73 In these cases, ventricular blood flow was simulated either as a generic sinusoidal waveform or using pulsatile pumps that could change the stroke volume, heart rate and systolediastole ratio. More sophisticated MCLs considered either part 12,[16][17][18][19]22,23,[30][31][32][33][34][35]46,48,52,60,61,65,66,74 or all the cardiovascular system 13,14,29,39,40,49,50,53,75 by including compliance chambers and variable resistances or, in few cases, by simulating it computationally.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate the latter event, named suction, a dedicated repfresentation of the ventricular anatomy, or of part of it, using a compliant material is needed. A few MCLs included a collapsible element representing only the ventricular apex 29–31 . In Figure 2 a scheme of the set up used by Rocchi et al 29 is shown.…”
Section: Medical Device Testing and Innovationmentioning
confidence: 99%
See 3 more Smart Citations